Analysis of the transcriptomic, metabolomic, and gene regulatory responses to Puccinia sorghi in maize. (28th February 2021) - Kim, Saet‐Byul; Van den Broeck, Lisa; Karre, Shailesh; Choi, Hoseong; Christensen, Shawn A.; Wang, Guan‐Feng; Jo, Yeonhwa; Cho, Won Kyong; Balint‐Kurti, Peter
Abstract: Common rust, caused by Puccinia sorghi, is a widespread and destructive disease of maize. The Rp1‐D gene confers resistance to the P. sorghi IN2 isolate, mediating a hypersensitive cell death response (HR). To identify differentially expressed genes (DEGs) and metabolites associated with the compatible (susceptible) interaction and with Rp1‐D ‐mediated resistance in maize, we performed transcriptomics and targeted metabolome analyses of P. sorghi IN2‐infected leaves from the near‐isogenic lines H95 and H95:Rp1‐D, which differed for the presence of Rp1‐D . We observed up‐regulation of genes involved in the defence response and secondary metabolism, including the phenylpropanoid, flavonoid, and terpenoid pathways. Metabolome analyses confirmed that intermediates from several transcriptionally up‐regulated pathways accumulated during the defence response. We identified a common response in H95:Rp1‐D and H95 with an additional H95:Rp1‐D‐specific resistance response observed at early time points at both transcriptional and metabolic levels. To better understand the mechanisms underlying Rp1‐D ‐mediated resistance, we inferred gene regulatory networks occurring in response to P. sorghi infection. A number of transcription factors including WRKY53, BHLH124, NKD1, BZIP84, and MYB100 were identified as potentially important signalling hubs in the resistance‐specific response. Overall, this study provides a novel and multifaceted understanding of the maize susceptible and resistance‐specific responses to P. sorghi . Abstract : We document the consequences of maize common rust infection of near‐isogenic resistant (a) and susceptible (b) maize lines at the transcription (c), metabolomic (d), and gene network (e) levels.